1991
DOI: 10.1095/biolreprod45.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Hyperlipidemia in Cattle Modifies the Intrafollicular Cholesterol Environment, Modulates Ovarian Follicular Dynamics, and Hastens the Onset of Postpartum Luteal Activity1

Abstract: Three experiments were conducted with female cattle during the postpartum period and during the estrous cycle to examine the effects of diet-induced hyperlipidemia on lipoprotein-cholesterol and triglyceride (TG) metabolism, ovarian follicular dynamics, and incidence of postpartum luteal activity. Dietary-lipid effects were examined independently of metabolizable energy intake. Feeding a high-lipid (HL) diet (8% total lipid) for the first 3 wk of the puerperium (Experiment 1) increased (p less than 0.0001) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 28 publications
5
53
1
6
Order By: Relevance
“…The saturated fatty acids in particular are bound on LDL, while the unsaturated ones are preferentially bound on albumin (Chung et al, 1995). Because LDL are absent in FF, these findings could account for the differences in concentration and composition of NEFA in FF compared to serum early post partum (Wehrman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The saturated fatty acids in particular are bound on LDL, while the unsaturated ones are preferentially bound on albumin (Chung et al, 1995). Because LDL are absent in FF, these findings could account for the differences in concentration and composition of NEFA in FF compared to serum early post partum (Wehrman et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in pregnancy rate at 45 d post insemination [5], ovarian follicle growth [6] and steroidogenesis [7] have all been reported. It has been suggested that the mechanism involves enhanced ovarian activity through the following: improved energy status [8], increased availability of cholesterol for steroid synthesis [9] and increased circulating insulin concentrations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Older studies often reported the positive influence of additional fat on ovarian activity, increased size of preovulatory follicles, and reduced pregnancy losses (Lucy et al 1991(Lucy et al , 1993Beam and Butler 1997;Ambrose et al 2006). Fat supplementation increased the concentration of total cholesterol in follicular fluid; this was associated with the fact that granulosa cells collected from follicles of supplemented cows showed increased progesterone secretion in vitro (Wehrman et al 1991). Ruminants treated with supplemental fat often had small increases in plasma concentrations of progesterone ).…”
Section: Discussionmentioning
confidence: 99%